2017
DOI: 10.1002/2016jc012206
|View full text |Cite
|
Sign up to set email alerts
|

Generation of internal solitary waves over a large sill: From Knight Inlet to Luzon Strait

Abstract: A fully nonlinear, nonhydrostatic numerical model is utilized to investigate the generation of Internal Solitary Waves (ISWs) upstream of the Knight Inlet sill. While an upstream hydraulic jump initiates the ISW generation and both hydraulic jump and upstream influence contribute to the generation, it is found that upstream influence is dominant and the hydraulic jump is not necessary for the ultimate generation of ISWs. Decreasing the tidal forcing or upstream sill width may render the flow subcritical (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Furthermore, the maximum topographic Froude number is just 0.3362 around the east ridge with the approach to the regime transition value 1/3, which ensures that the nonlinear hydraulic jump can grow with lee waves on the east of the east ridge. All of the above can explain the generation of the internal tide beam and hydraulic jump well in our simulation and confirm the mixed tidal lee wave regime in the Luzon Strait (Chen et al, 2017).…”
Section: Nonlinear Internal Waves In a Double-ridge Systemsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the maximum topographic Froude number is just 0.3362 around the east ridge with the approach to the regime transition value 1/3, which ensures that the nonlinear hydraulic jump can grow with lee waves on the east of the east ridge. All of the above can explain the generation of the internal tide beam and hydraulic jump well in our simulation and confirm the mixed tidal lee wave regime in the Luzon Strait (Chen et al, 2017).…”
Section: Nonlinear Internal Waves In a Double-ridge Systemsupporting
confidence: 84%
“…A significant hydraulic jump can appear with the isotherm fluctuation up to roughly 200 m on the eastern side, which indicates the formation of lee waves to a certain extent. The above internal wave generation due to tide-topography interactions can be described with the below nondimensional parameters at the source: (1) the tidal excursion parameter ε = U 0 /Lω, which can be associated with the generation of an internal tide beam under critical or supercritical topography, where U 0 is barotropic current amplitude from the far field and L is the characteristic length for topography (Garret and Kunze, 2007;Chen et al, 2017); (2) the Froude number F r = U/c and its topographic form F r z = ω/N (dH /dx), in which c is the mode-1 linear speed for the eigenvalue problem (Legg and Adcroft, 2003; see Appendix B). Specifically, Legg and Klymak (2008) found that the nonlinear hydraulic jump will develop with lee wave generation when F r z < 1/3.…”
Section: Nonlinear Internal Waves In a Double-ridge Systemmentioning
confidence: 99%
“…We classified the warm and cold episodes of the ENSO events following the method described by Chu et al (2017) 2014). Numerical experiments and observations have both revealed that the structure of stratification affects the generation of ITs (Chen et al, 2017;Guo et al, 2012;Jeon et al, 2014). To explore the impact of stratification on the vertical structure of ITs, we plotted year-averaged HKE of different modes in El Niño and La Niña years (Figures 7b-7e).…”
Section: The Modulation Of Its By Ensomentioning
confidence: 99%
“…In the framework of resonant generation, this characteristic length is considered here as a proxy for the interfacial disturbances originating near forcing bathymetry as a result of the stratified flow. Note that the characteristic length of these interfacial disturbances usually compares with the already developed packets rather than with their individual waves (e.g., see Farmer andArmi, 1999, andChen et al, 2017). Nonetheless, changing this length scale results in changes at most of about 0.1 m s -1 in c in Equation 1 (when considering a depth of 500 m, where most of the observations were made).…”
Section: Resonant Generation Of Iwsmentioning
confidence: 99%